الفكر الابتكاري والهوية في التصميم الداخلي - لفته، رجاء سعدي (جامعة بغداد - كلية التربية ابن رشد, 2012)
يعنى البحث بدراسة الفكر الابتكارى وعلاقته الموضوعية بالهوية للفضاءات الداخلية , إذ تناولت الباحثة في هذا البحث – أنواع التفكير : الحسي والمجرد والاستدلالي والناقد مع المفاهيم التي عرفت الهوية , وماهية هوية الفكر مع ربطها بخصائص التصميم الداخلي لغرض التعرف إلى الهوية المعاصرة بالرجوع إلى المراجع التي تطرقت لذلك ,وكشف حاصل تفاعل القيم الإنسانية مع إحساس الفرد للانتماء إلى المكان الجغرافي الذي يدل على هويته. إذ من المعروف أن الهوية تولد من رحم الفكر , وروح هذه الهوية هي روح الفكر الذي أنتج الحضارة والثقافة , وقد تطرقت الباحثة كذلك إلى الحاجة إلى الهوية كحاجات فسيولوجية , وحاجات أمنية , وحاجات اعتبارية , وحاجات معرفية وجمالية , مع حاجات تحقيق الذات . ولابد من توفير نتاج يتوافق مع هذه الحاجات والتي تحدث في تغيير بيئة الفرد وأسلوبه في المعيشة , وربطت ذلك بالحاجة الجمالية مع عدم إغفال الإرث الحضاري والثقافي للإدراك الجماعي بهدف التعبير عن هوية المبنى الذي يمتاز بشخصية التفرد والخصوصية المرتبطة بالمكان والزمان , ثم اختتمت البحث في دور الهوية في التصميم الداخلي الذي يتفرد كهوية في طابعه الوطني , والاقليمى وشخصية المصمم الذي هو ابن تلك الحضارة وما بين تفكيره الابتكارى المؤثر مع استلهامه للحضارة والتراث العربي الذي ينتمي إليه وعززت ذلك بأمثلة وشواهد من أشهر المصممين العراقيين والعرب. \ واعتمدت الباحثة على منهج البحث الأساسي المكتبي المعمول به في البحوث النظرية الفكرية وهو يختلف عن المنهج التجريبي , وذلك بالرجوع إلى المراجع والمصادر التي تطرقت إلى كل المفهومين المترادفين وهما الفكر الابتكارى والهوية مع توضيح العلاقة الموضوعية بينهما , فضلا عن الإشارة إلى الموهوبين الذين برزوا كمصممين ومعماريين وذلك بالرجوع إلى الانترنت مع الكتب والدوريات التي كانت من وسائل جميع بيانات هذا البحث . Means research study thought innovation and its relationship to the substantive identity of the spaces of the Interior, as dealt with the researcher in this research - types of thinking: sensory and abstract and inferential and critical with the concepts that defined identity, and what the identity of thought linked to the characteristics of interior design for the purpose of getting to know the identity of contemporary reference to the references that touched so , revealing the interaction of human values holds with an individual sense of belonging to the place which indicates the geographical identity. It is known that the identity born from the womb of thought, and the spirit of this identity is the spirit of Thought produced a civilization and culture, has touched the researcher as well as to the need for identity requirement physiological and security needs and the needs of corporate, and the needs of cognitive and aesthetic, with the needs of self-realization. It must provide the product is compatible with these needs, which occur in changing the environment of the individual and his style of living, and correlated this to the need for aesthetic, not to mention legacy of civilization and cultural awareness group in order to express the identity of the building, which is characterized by personality exclusivity and privacy associated with the place and time, and then concluded research on the role of identity in interior design which is unique in nature as the identity of the national, regional and character designer who is the son of that civilization, and innovative thinking among influential with inspired of civilization and the Arab heritage that belongs to him and strengthened it with examples and evidence of the most famous designers of Iraqis and Arabs \ And adopted a researcher on the research methodology basic desktop in force in the theoretical research of intellectual is different from the experimental method, in reference to the references and sources that dealt with each of the two concepts Synonymous They thought innovation and identity with the clarification of the relationship objectivity between them, as well as reference to the talented people who emerged as designers and architects by referring to the Internet with books and periodicals, which was a means of collecting data for this research
Keywords: التفكير الابتكاري -- الهوية -- القدرات العقلية -- الإبداع الفني -- التصميم الداخلي